Sorbents from vegetative waste and nanotubes - Elnaggar, Essam; Krichkovskaya, Lidiya (Національний технічний університет "Харківський політехнічний інститут", 2019)
Ashes of sunflower peel after burning under oxygen deficiency have sorption activiti. It was used to obtain a sorbent capable to entrap oil products. Its capaciti in laboratory conditions takes 1,5-3 g/g, but efficiency of water purification can reach 90% and more. Black ashes received after pyrolysis of sunflower peel possesses excellent sorption properties and it isn't inferior to the best grades of active coal by its quality. Surfacing of water or sewage with the offerd sorbent is carried out at temperature from 0 to 100 C. It's possible to provide reactivation of the sorbent used by treating with hydrocarbon solvents (petrol, kerosene, etc.) or with other organic solvents (alcohols, etc.) or their mixtures.
Keywords: sorption; coal; oil; water; ecology; sun flower peel; nanotubes